PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN GAMIFIKASI DI KELAS IV C - Meyda Rohaniah; Gita Ulfi Noorachman; Nilung Arum Kinanti; Yanuar Presti Wahyu Puspitaningtyas; Honest Ummi Kaltsum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve IPAS learning outcomes through the use of gamification in the form of educaplay and puzzle interactive media. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of four stages. The research was conducted in two cycles, with lesson plans developed jointly by teachers and researchers in each cycle. This research was conducted at SD Muhammadiyah 8 Jagalan Surakarta for students in class IV C, with biodiversity material in the odd semester of the 2024/2025 school year. The population involved in this study were 21 students. Data collection techniques include tests (pretest and posttest) and non-tests in the form of observation, interviews, and documentation. The results showed an increase in the average score of learning outcomes, from cycle I, the increase was 29%. Furthermore, cycle II showed a surge in learning outcomes by 53%. Because as many as 86% of students achieved a score of more than or equal to 75 (KKTP), this research was declared successful.